Wear analysis and cyclic fatigue resistance of electro discharge machined NiTi rotary instruments - F. Iacono; C. Pirani; L. Generali; P. Sassatelli; C. Nucci; M.G. Gandolfi; C. Prati (Ariesdue, 2016)
Aim: To evaluate the wear of new rotary instruments produced via electro discharge machining and to test their fatigue resistance. Methodology: Twenty-one HyFlex EDM (Coltène/Whaledent, Switzerland) files were used for laboratory instrumentation of curved root canals of extracted teeth. Superficial characteristics were analyzed pre- and postoperatively by scanning electron microscopy (SEM) (JSM-5200, JEOL, Tokyo, Japan) at same points and with same angulations to identify the wear features. Number of fractures, microcracks blunt/disruption of cutting edge and tip deformations were reported. Twenty HyFlex EDM and 20 HyFlex CM (Coltène/Whaledent, Switzerland) were subjected to cyclic fatigue test in a 70° artificial metal canal. Results were statistically analyzed using Mann-Whitney tests. Results: No fractures were registered during laboratory canal instrumentation. No wear and no degradation of the 25.12 and 25.08 files were reported. Slight plastic deformations were only observed in three 10.05 files. The cyclic fatigue test revealed a significant increase of fatigue resistance of EDM files compared to CM (p = 0.0001). Conclusions: The typical irregular surface of HyFlex EDM remained unaffected after multiple uses, confirming a high wear resistance. The new manufacturing process of electrical discharge machining had a substantial impact on fatigue lifetime of EDM files when compared with HyFlex CM. Within limitations of the present in vitro results, EDM files appeared suitable in shaping severely curved canals.